In vivo bone strain in the mandibular corpus of Sapajus during a range of oral food processing behaviors. Issue 98 (September 2016) - Ross, Callum F.; Iriarte-Diaz, Jose; Reed, David A.; Stewart, Thomas A.; Taylor, Andrea B.
Abstract: It has been hypothesized that mandibular corpus morphology of primates is related to the material properties of the foods that they chew. However, chewing foods with different material properties is accompanied by low levels of variation in mandibular strain patterns in macaques. We hypothesized that if variation in primate mandible form reflects adaptations to feeding on foods with different material and geometric properties, then this variation will be driven primarily by differences in oral food processing behavior rather than differences in chewing per se. To test this hypothesis, we recorded in vivo bone strain data from the lateral and medial surfaces of the mandibular corpus during complete feeding sequences in three adult male Sapajus as they fed on foods with a range of sizes and material properties. We assessed whether variation in mandibular corpus strain regimes is associated with variation in feeding behaviors and/or chewing on different foods, and we quantified the relative variation in mandibular corpus strain regimes associated with chewing on foods of different material properties versus a range of oral food processing behaviors (incisor, premolar, and molar biting; pulling on incisors; mastication). Feeding behavior had a significant effect on mandibular corpus strain regimes, as did chewing side and the cycle number in a feeding sequence. However, food type had weaker effects and usually only through interaction effects with chewing side and/or cycle type. Strain regimes varied most across different chew sides, then across different behaviors, and lastly between mastication cycles on different foods. Strain magnitudes associated with premolar, molar, and incisor biting were larger than those recorded during mastication. These data suggest that intra- and inter-specific variation in mandible morphology is a trade-off between performance requirements of different oral food processing behaviors and of variation in chewing side, with direct effects of food type being less important.